2009
DOI: 10.1007/s12192-009-0103-3
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia in the febrile range induces HSP72 expression proportional to exposure temperature but not to HSF-1 DNA-binding activity in human lung epithelial A549 cells

Abstract: Expression of heat shock proteins (HSPs) is classically activated at temperatures above the physiologic range (≥42°C) via activation of the stress-activated transcription factor, heat shock factor-1 (HSF-1). Several studies suggest that less extreme hyperthermia, especially within the febrile range, as occurs during fever and exertional/environmental hyperthemia, can also activate HSF-1 and enhance HSP expression. We compared HSP72 protein and mRNA expression in human A549 lung epithelial cells continuously ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…In an earlier study, we found that exposing RAW cells to 40°C failed to activated Hsp70 mRNA expression (45), but the cells were only heated for 30 min in the previous study. The results of the two studies are consistent with our observation that Hsp70 induction at less extreme hyperthermia requires longer exposure time (27). In the present study, we showed that co-treating RAW cells with TLR4 (LPS) or TLR2/1 (Pam3cys) agonists greatly augmented Hsp70 expression in FRT-exposed RAW cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In an earlier study, we found that exposing RAW cells to 40°C failed to activated Hsp70 mRNA expression (45), but the cells were only heated for 30 min in the previous study. The results of the two studies are consistent with our observation that Hsp70 induction at less extreme hyperthermia requires longer exposure time (27). In the present study, we showed that co-treating RAW cells with TLR4 (LPS) or TLR2/1 (Pam3cys) agonists greatly augmented Hsp70 expression in FRT-exposed RAW cells.…”
Section: Discussionsupporting
confidence: 92%
“…We have previously shown that exposure to FRT (38.5-39.5°C) is sufficient to activate HSF1 and induce expression of Hsp70 but at much lower levels than what occurs in response to temperatures above 42°C (27,40). In the current study, we have extended these findings by showing that stimulating TLR-dependent signaling pathways while exposing cells to FRT or HS greatly augments Hsp70 expression and its release into the extracellular microenvironment in both in vitro cell culture and in vivo in an intratracheal LPS-induced acute lung injury model.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our previous studies have demonstrated that modest deviations from normothermia can alter stressinduced and proinflammatory signaling pathways, including heat shock factor-1 (HSF-1), p38 MAP kinase, and NFκB (Fairchild et al 2004(Fairchild et al , 2005Tulapurkar et al 2009Tulapurkar et al , 2012) and modify expression of important genes. We have previously identified several mechanisms by which shifts in temperature within the physiologic range modify gene transcription (Singh et al 2002Cooper et al 2010a, b).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, hyperthermia increases the efficacy of chemotherapeutic agents such as oxaliplatin or melphalan when used in combination with TRAIL, killing the CX-1 colorectal cancer cells more effectively (Yoo and Lee, 2008). Furthermore, it promoted an antitumor immune response by activation of HSP70 (Tulapurkar et al, 2009). …”
Section: Introductionmentioning
confidence: 99%